1990
DOI: 10.1128/iai.58.4.909-913.1990
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the functionally active complement receptor for iC3b but not for C3d on an avirulent mutant of Candida albicans

Abstract: Pseudohyphae of Candida albicans bear surface receptors for iC3b and C3d. In order to determine a possible role for these receptors in the pathogenesis of candidiasis, a spontaneous C. albicans mutant, m-10, which exhibits reduced ability to adhere in vitro to fibrin platelet clots and epithelial cells or to cause endocarditis in a rabbit model, and its parent wild-type (wt) strain were compared for receptor expression in rosetting assays with sheep erythrocytes carrying iC3b (EAC1423bi) or C3d (EAC1423d). An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 15 publications
1
45
0
Order By: Relevance
“…57,58 Virulent strains of C. albicans produce higher amounts of the CR3-homologue than avirulent mutants, and the expression of the cloned molecule in Saccharomyces cerevisiae leads to the adhesion of this normally nonadherent yeast to human epithelial cells. 59,60 An additional role for the fungal CR3-like protein was proposed by Moors et al [61] by binding C. albicans cells to erythrocytes, it might help to acquire the vitally important iron out of blood ( Fig. 2).…”
Section: Candidal Complement Evasion and Aberrant Usage Of Complementmentioning
confidence: 95%
“…57,58 Virulent strains of C. albicans produce higher amounts of the CR3-homologue than avirulent mutants, and the expression of the cloned molecule in Saccharomyces cerevisiae leads to the adhesion of this normally nonadherent yeast to human epithelial cells. 59,60 An additional role for the fungal CR3-like protein was proposed by Moors et al [61] by binding C. albicans cells to erythrocytes, it might help to acquire the vitally important iron out of blood ( Fig. 2).…”
Section: Candidal Complement Evasion and Aberrant Usage Of Complementmentioning
confidence: 95%
“…Thus, the C3bi opsonin may be diverted away from phagocytes onto Candida expressing CR3 [23,24]. Alternatively, this functionally active CR3 receptor on Candida aibicans, as a member of the integrin receptor superfamily, may mediate the attachment of Candida to mammafian cells [25].…”
Section: Phagocytosismentioning
confidence: 99%
“…The difficulty of obtaining mutant phenotypes in diploid organisms such as C. albicans and the concomitant loss and regain of germ tube formation and surface expression of certain antigens suggested that a single locus was involved. Mutants deficient in binding iC3b and C3d, activities preferentially expressed on hyphal extensions, are able to form germ tubes [20][21] and thus germ tube formation is not dependent on expression of either of these determinants. On the other hand conditions which inhibit synthesis [22] or deposition [11] of a putative structural protein of the hyphal wall reduce germ tube formation and suggest that synthesis of one or more preferentially expressed proteins is not dispensable.…”
Section: Discussionmentioning
confidence: 99%